2012
DOI: 10.1093/carcin/bgs359
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl isothiocyanate induces protective autophagy in human prostate cancer cells via inhibition of mTOR signaling

Abstract: Benzyl isothiocyanate (BITC) is a dietary chemopreventive agent that inhibits the growth of various human cancer cells by causing apoptotic cell death. In this study, we demonstrate that BITC not only induces apoptosis but also induces autophagy in human hormone-sensitive (Rv1) and -refractory (PC3) prostate cancer cells. In BITC-treated cells, the induction of autophagy was detected by monitoring the processing of an autophagy marker protein, microtubule-associated protein 1 light chain 3 (LC3), the aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 38 publications
4
55
1
Order By: Relevance
“…Abundance of nutrients, including growth factors, glucose, and amino acids activate mTOR and suppress autophagy, whereas nutrient deprivation could inhibit mTOR and promote autophagy [21,63]. PI3K/AKT lay upstream of mTOR, and activated AKT inhibited autophagy through activating mTOR [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Abundance of nutrients, including growth factors, glucose, and amino acids activate mTOR and suppress autophagy, whereas nutrient deprivation could inhibit mTOR and promote autophagy [21,63]. PI3K/AKT lay upstream of mTOR, and activated AKT inhibited autophagy through activating mTOR [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, protective autophagy that is induced by benzyl isothiocyanate (BITC), a dietary chemo-preventive agent, induces apoptosis when 3-MA inhibits BITC-mediated autophagy [104]. The chemo-preventive effects of dietary phytochemicals on malignant tumors have been studied extensively due to a relative lack of toxicity.…”
Section: Chemopreventive Dietary Agents In Managing Protective Autophagymentioning
confidence: 99%
“…Likewise, BITC also suppresses PI3K (Tyr-458), PDK1 (Ser-241), and mammalian target of rapamycin (mTOR) (Ser 2448) [16]. BITC also inhibits mTOR signaling in prostate cancer cells [28]. Importantly, these studies have shown that BITC has very negligible effect on the growth of normal human pancreatic ductal epithelial 6 cells, indicating specificity of BITC toward cancer cells.…”
Section: Cancer Cell Progressionmentioning
confidence: 87%